Challenging the Eco-Islamic Decoupling: A Critical Analysis of Strategic Gaps Between Government Mandates and Green Madrasah SWOT Capacity toward Institutional Transformation - Mustafa Mustafa; Darul Ilmi; Yanti Elvita; Syahrur Ramli; Mega Adyna Movitaria; M Fauzil Azra; Syafrul Nalus (Yayasan Darussalam Bengkulu, 2026)
This study investigates the profound Eco Islamic decoupling within Islamic education, focusing on the strategic gap between ambitious government green madrasah mandates and the localized operational capacities of schools. The core problem stems from top-down, unfunded environmental regulations that systematically ignore the specific SWOT profiles of educational institutions. Resolving this friction is highly urgent, as coercive mandates currently breed severe institutional exhaustion and theoretical stagnation of eco-theological values, preventing real change. Therefore, this research aims to critically analyze the structural root causes of green madrasah policy failures and deeply uncover the underlying mechanisms of organizational transformation decoupling. Utilizing a critical qualitative methodology, the study employs in-depth institutional ethnography at MTsN 3 Lima Puluh Kota. Data were rigorously collected over six months through prolonged non-participant observation, semi-structured interviews via targeted purposive sampling, and comprehensive document analysis, followed by thematic transformation analysis and source triangulation. The results reveal a catastrophic alignment failure: government mandates function as coercive technocratic mechanisms, while the green madrasah experiences them as severely underfunded administrative burdens. Consequently, schools engage in performative compliance and defensive decoupling such as fabricating sustainability reports and prioritizing superficial visual greening as rational institutional survival strategies rather than ideological rejection. The discussion concludes that authentic Eco-Islamic institutional transformation remains mathematically impossible without radically shifting from uniform, unfunded bureaucratic audits toward localized, resource-backed empowerment frameworks specifically tailored to individual green madrasah capabilities.